Coronary artery disease risk factors in bus drivers - Elder dos Santos Gonçalves; Raimeyre Marques Torres; Tiago Cardoso Peixinho; Cléa Conceição Leal Borges (Universidade Federal da Bahia, 2014)
This study aimed to identify risk factors for coronary artery disease (CAD) in drivers of public mass transportation in the municipality of Salvador (Bahia) and knowledge of these as a form of prevention. Descriptive study. Convenience sample. Descriptive analysis. 100 drivers full time employees, predominantly median age of 38 years, color / black ethnicity, average schooling, family income between 1-3 minimum wages, with 4-6 dependent on residence, alcohol consumption were approached 65.0% , sedentary 73.0% overweight and 52.0% reported stress in the workplace in 63.0%. Most respondents have knowledge regarding the risk for development of CHD factors, but still retains habits that discourages prevention. The nurse, student health, should ensure that bus drivers and other workers exposed to occupational risks and risk for CAD, a better quality of life factors.